Penerapan Green Productivity Pada UMKM Aneka Batik Pamekasan - Muhamad Khoirul Alfa; Indra Cahyadi; Ika Deefi Anna (Prosiding Seminar Nasional Teknoka, 2023)
Aneka Batik is a micro, small and medium enterprise that produces hand-written batik typical of the Pamekasan region. Waste from batik soaking is discharged directly into the ground and sewers. The impact produced by this batik waste is that it causes water pollution and causes corrosion of the soil. One approach that can help Aneka Batik MSMEs to reduce environmental impacts and increase productivity is the application of Green Productivity. With the application of Green productivity we can find out the level of productivity, find out the Enviromental performance Indicator (EPI) and find out alternative solutions for improvement. Based on the calculation, it is known that the resulting EPI index value is -10.382. To increase the EPI value, the alternative solution used is to replace textile dyes with natural dyes. This dye replacement is expected to provide savings of Rp 405,375 and an increase in productivity value of 0.03%.